2022
DOI: 10.1007/s10067-022-06255-3
|View full text |Cite
|
Sign up to set email alerts
|

Apremilast retention rate in clinical practice: observations from an Italian multi-center study

Abstract: Objective There are few real-world setting studies focused on apremilast effectiveness (i.e., retention rate) in psoriatic arthritis (PsA). The main aim of this retrospective observational study is the assessment of apremilast 3-year retention rate in real-world PsA patients. Moreover, the secondary objective is to report the reasons of apremilast discontinuation and the factors related to treatment persistence. Methods In fifteen Italian rheumatological referral centers, all PsA consecutive patients who recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Interestingly, recent studies have discovered similar sex differences in patients treated with IL‐17 inhibitors in a real‐world setting and in post hoc analyses of randomized controlled trials (RCTs) of Janus kinase inhibitors after three months of treatment 8,40 . However, a real‐world study on apremilast did not identify sex differences in retention rates 41 . In addition, the preliminary findings from post hoc analyses of the EXCEED RCT suggested that women receiving an IL‐17 inhibitor experienced a better clinical response than those treated with a TNFi.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, recent studies have discovered similar sex differences in patients treated with IL‐17 inhibitors in a real‐world setting and in post hoc analyses of randomized controlled trials (RCTs) of Janus kinase inhibitors after three months of treatment 8,40 . However, a real‐world study on apremilast did not identify sex differences in retention rates 41 . In addition, the preliminary findings from post hoc analyses of the EXCEED RCT suggested that women receiving an IL‐17 inhibitor experienced a better clinical response than those treated with a TNFi.…”
Section: Discussionmentioning
confidence: 98%
“…8,40 However, a real-world study on apremilast did not identify sex differences in retention rates. 41 In addition, the preliminary findings from post hoc analyses of the EXCEED RCT suggested that women receiving an IL-17 inhibitor experienced a better clinical response than those treated with a TNFi. This difference was not observed in men.…”
Section: Discussionmentioning
confidence: 99%
“…The analyzed population is part of the BIRRA (Biologics Retention Rate Assessment) project, an observational retrospective study [15]. All PsA consecutive patients from fifteen Italian rheumatological referral centers were screened.…”
Section: Patientsmentioning
confidence: 99%
“…Among the three-hundred fifty-six PsA patients included in our previous report [15], two-hundred ninety-three with a follow-up period of at least one year were enrolled in the study. One-hundred twenty-six (43%) patients were male.…”
Section: Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation